2014
DOI: 10.1007/s40279-014-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inter-Set Rest Intervals on Resistance Exercise-Induced Muscle Hypertrophy

Abstract: Due to a scarcity of longitudinal trials directly measuring changes in muscle girth, previous recommendations for inter-set rest intervals in resistance training programs designed to stimulate muscular hypertrophy were primarily based on the post-exercise endocrinological response and other mechanisms theoretically related to muscle growth. New research regarding the effects of inter-set rest interval manipulation on resistance training-induced muscular hypertrophy is reviewed here to evaluate current practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 61 publications
2
34
0
4
Order By: Relevance
“…With this said, many authors have proposed that rest intervals of 30–60 seconds are optimal because they result in the greatest exercise-induced elevations in selected anabolic hormones, notably growth hormone (de Salles et al, 2009; Willardson, 2006). The current literature does not support this notion per se (Henselmans & Schoenfeld, 2014); however, many experienced practitioners anecdotally report more hypertrophic gains with shorter rest intervals.…”
Section: Pragmatic Resistance Exercise Advice For Patients and The Prmentioning
confidence: 88%
“…With this said, many authors have proposed that rest intervals of 30–60 seconds are optimal because they result in the greatest exercise-induced elevations in selected anabolic hormones, notably growth hormone (de Salles et al, 2009; Willardson, 2006). The current literature does not support this notion per se (Henselmans & Schoenfeld, 2014); however, many experienced practitioners anecdotally report more hypertrophic gains with shorter rest intervals.…”
Section: Pragmatic Resistance Exercise Advice For Patients and The Prmentioning
confidence: 88%
“…The durations of inter-set rest periods are not accounted for in these equations. The inter-set recovery duration is known to be a primary determinant of the overall intensity of a resistance training session [5], and has a marked effect on physiological responses such as blood lactate concentration [18]. Additionally, measures of volume load do not take into account repetition velocity, which also contributes to the overall intensity of resistance exercise.…”
Section: Volume Loadmentioning
confidence: 99%
“…Concerning these findings, duration of rest intervals may reflect directly on the magnitude of metabolic stress. In a review study, researchers demonstrated that short interval sets (less than one minute) are essential in increasing blood lactate and GH production, mainly because of insufficient recovery of phosphocreatine and H + accumulation[36]. …”
Section: Resistance Trainingmentioning
confidence: 99%